Survivability of Kluyveromyces marxianus Isolated From Korean Kefir in a Simulated Gastrointestinal Environment - Youn, Hye-Young; Kim, Dong-Hyeon; Kim, Hyeon-Jin; Bae, Dongryeoul; Song, Kwang-Young; Kim, Hyunsook; Seo, Kun-Ho (Frontiers in Microbiology, 2022)
Kluyveromyces marxianus accounts for >90% of the yeast population of kefir, and recently, its probiotic potential has been actively explored with a focus on its health benefits and safety. Herein, the survivability of five kefir-isolated K. marxianus strains (A1–A5) in a simulated gastrointestinal (GI) environment was evaluated and compared with those of commercial probiotic yeast, Saccharomyces boulardii MYA-796. To further explore the potential to survive in the host GI tract, biochemical activities, hydrophobicity assay, biofilm formation, auto-aggregation analysis, and phenol tolerance of the strains were assessed. K. marxianus A4 exhibited the best survivability among all tested strains, including the clinically proven probiotic yeast strain S. boulardii MYA-796 (p = 0.014) in the artificial GI tract ranging from pH 2.0 to 7.5. In addition, the five K. marxianus strains and S. boulardii MYA-796 displayed different assimilation of lactose, xylitol, D-sorbitol, and DL-lactate, indicating that K. marxianus metabolized a wide range of substances and, thus, might be more feasible to nourish themselves in the host GIT for survival. K. marxianus strains showed a greater hydrophobicity of cell surface, abilities to biofilm formation and auto-aggregation, and phenol tolerance than S. boulardii MYA-796, suggesting greater potential for survival in the host GI tract.